Search for electroweak production of charginos and neutralinos in WH events in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (10.1007/JHEP11(2017)029, 2017)
Results are reported from a search for physics beyond the standard model in proton-proton collision events with a charged lepton (electron or muon), two jets identified as originating from a bottom quark decay, and significant imbalance in the transverse momentum. The search was performed using a data sample corresponding to 35.9 fb−1 , collected by the CMS experiment in 2016 at √ s = 13 TeV. Events with this signature can arise, for example, from the electroweak production of gauginos, which are predicted in models based on supersymmetry. The event yields observed in data are consistent with the estimated standard model backgrounds. Limits are obtained on the cross sections for chargino-neutralino (χe ± 1 χe 0 2 ) production in a simplified model of supersymmetry with the decays χe ± 1 → W±χe 0 1 and χe 0 2 → Hχe 0 1 . Values of m χe ± 1 between 220 and 490 GeV are excluded at 95% confidence level by this search when the χe 0 1 is massless, and values of mχe 0 1 are excluded up to 110 GeV for m χe ± 1 ≈ 450 GeV.